Anti-biofilm Potential of Elletaria cardamomum Essential Oil Against Escherichia coli O157:H7 and Salmonella Typhimurium JSG 1748 - Abdullah,; Asghar, Ali; Algburi, Ammar; Huang, Qingrong; Ahmad, Talha; Zhong, Hao; Javed, Hafiz U.; Ermakov, Alexey M.; Chikindas, Michael L. (Frontiers in Microbiology, 2021)
Foodborne pathogens, microbial recurrent infections, and antibiotics resistance have driven researchers to explore natural compounds as safe alternative antimicrobials. In this study, the chemical profile, antimicrobial, and mutagenic activities of the Elletaria cardamomum essential oil were investigated. GC-MS analysis identified the major bioactive components as α-terpinyl acetate, 1,8-cineole, linalool acetate, and sabinene, at concentrations of 34.95, 25.30, 8.13, and 5.48% respectively, of the essential oil’s content. In regards to antimicrobial activity, the minimum inhibitory concentration of green cardamom essential oil was 1% against Escherichia coli O157:H7 and Pseudomonas aeruginosa ATCC 14213. Green cardamom essential oil, when used at concentrations of 0.015, 0.031, 0.062, and 0.125% (v/v) prevented biofilm formation of Escherichia coli O157:H7 by 64.29, 65.98, 70.41, and 85.59%, respectively. Furthermore, these concentrations inhibited 6.13, 45.50, 49.45, and 100%, respectively, of Salmonella Typhimurium JSG 1748 biofilm. A mutagenicity assay confirmed that green cardamom essential oil has no demonstrable mutagenic activity against the tested strains. The study’s findings suggest that green cardamom derived bioactive compounds are safe organic antimicrobials, effective in controlling biofilm formation by Gram-negative pathogens. Moreover, such compounds could possibly be used in the food industry (e.g., bakery, dairy, meat, and other food products) as a safe alternative to chemical preservatives (antimicrobials) to enhance shelf life by improving the antimicrobial status while at the same time imparting a pleasant and appealing aroma for consumers.